AB1035 Ultra-low dose anti-interleukin1 in chronic gout: a safe and successful combination therapy with low dose colchicine and urate lowering agents. (12th June 2018) - Capassoni, M.; Galluccio, F.; Matucci Cerinic, M.
Abstract : Background: Gout is the most common inflammatory arthritis in humans; is caused by deposition of monosodium urate (MSU) crystals within and around joints. Left untreated, a more chronic course may develop, characterised by persistent inflammation and visible MSU deposits (tophi), bone erosion, irreversible joint damage, and significant disability(. 1 Management is based on two strategies: treating pain and inflammation with NSAIDs, steroids and colchicine and preventing flares and urate deposition with urate-lowering therapy(. 2 For many patients, standard treatments are ineffective or contraindicated, mainly due to comorbidities(. 3 The main mechanism of crystal-induced inflammation is interleukin 1β (IL-1β)(, 4 which strengthens the relevance of targeting IL-1β in patients with crystal-induced arthritis. Selective blockade of IL-1β has shown to drastically reduce pain, inflammation and risk of flares. Three biologic therapies inhibits IL-1β and have been studied for difficult to treat acute gouty arthritis flares: anakinra, rilonacept and canakinumab.(. 5–6 Objectives: Evaluate the efficacy of low dose anti-IL1 inhibitors administer by sublingual route in gout arthritis with remitting course that cannot be completely controlled with standard therapy regimens Methods: Inclusion criteria was diagnosis of chronic gouty arthritis with remitting course (acute flares in patients with chronic gout and no inter-critical period), high CRP levels and need of chronic assumptions of NSAIDs or steroids, with flare at suspension. 20 patients fulfilled the criteria (exclusion criteria: intolerance to the study drug, poor compliance to therapies or diet, hyperuricemia, end stage renal disease) The study consist of two consecutive parts. An observational part were patients are treated for 6 months with 0.5–1 mg/daily of colchicine and 300 mg/daily of allopurinol. They performed visits at baseline, 3 and 6 months and we collected data about blood tests, VAS score, number of flares, compliance to therapy and adverse events. An experimental part were we added GUNA anti-IL1 (an infinitesimal dilution of anakinra that has has a concentration of 10 fg/mL) 20 drops administered SL. Again patients performed visits at baseline (which coincides with the last visit of the observational phase), 3 and 6 months and we collected the same kind of data. Results: At 6 months after introduction of GUNA anti-IL1 all patients, except 1, experienced no flares of disease, levels of CRP became negative and VAS pain scale was significantly reduce (CRP level p<0.0001; VAS p<0.0001). NSAIDs and steroid consumption was significantly reduced. No adverse events happened Conclusions: Ultra-low dose of anti-IL1 agents added to standard therapy is an effective and safe way to achieve disease remission References: [1] Richette P Gout. Lancet2009, 375:318–328. [2] Zhang W EULAR evidence based recommendations for gout. Part II: management. Ann Rheum Dis2006, 65:1312–1324. [3] N, Schlesinger Difficult-to-treat gouty arthritis: a disease warranting better management. Drugs. 2011Jul 30;71(11):1413–39. [4] Martinon F Gout-associated uric acid crystals activate the NALP3 inflammasome. Nature2006, 440:237–241. [5] So A A pilot study of IL-1 inhibition by anakinra in acute gout. Arthritis Res Ther2007, 9:R28. [6] Chen K Anakinra's efficacy is variable in refractory gout: report of ten cases. Semin Arthritis Rheum2010, 40:210–214. Disclosure of Interest: None declared